Intrinsically Disordered Proteins and Their “Mysterious” (Meta)Physics - Uversky, Vladimir N. (Frontiers in Physics, 2019)
Recognition of the natural abundance and functional importance of intrinsically disordered proteins (IDPs) and hybrid proteins containing ordered and intrinsically disordered protein regions (IDPRs) is changing protein science. IDPs and IDPRs; i.e., functional proteins and protein regions without unique structures, are commonly found in all organisms, where they have crucial roles in various biological processes. Disorder-based functionality complements functions of ordered proteins and domains. However, by virtue of their existence, IDPs/IDPRs, which are characterized by the remarkable conformational flexibility and structural plasticity, break multiple rules elaborated over the years to explain structure, folding, and functionality of well-folded proteins with unique structures. Despite the general believe, which dominated in protein science for more than a century, that unique biological functions of proteins require unique 3D-structures, structure-less IDPs/IDPRs are functional, being able to perform impossible tricks and to be engaged in biological activities, which are improbable for ordered proteins. With their exceptional spatio-temporal heterogeneity and high conformational flexibility, IDPs/IDPRs represent complex systems that act at the edge of chaos and are specifically tunable by various means. In this article, some of the wanders of intrinsic disorder are discussed as illustrations of their ‘mysterious’ (meta)physics.